From livestock to game farming : farmers understandings of land use changes, sustainable agriculture and biodiversity conservation in the Ubuntu Municipality, South Africa - Manyani, Charmaine Rudo Sanelisiwe (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.